Performance testing of a proposed design energy installation system for vehicle’s wind turbine - Mohd, Sofian; Rosly, Nurhayati; Basuno, Bambang; Mohd Fikri, Mohd Masrom; Abdul Ghafir, Mohammad Fahmi (IOP Publishing, 2019)
The present study considered the performance analysis of a new proposed design of a vehicle’s wind turbine energy installation system. A test is conducted on the energy conversion and storage system that have been built to evaluate its performance and the capability. The result shows that the power that is generated by the system is directly proportional to the speed of the alternator. The time taken for charging a battery is also recorded and it is found that it takes about 2 to 3 hours to fill the 12-volt battery depending on the size and capacity of the battery used. The power generated for the system is 20.4 watt and 120.5 watt at 60 km/h and 120 km/h respectively. From the analysis that has been done, the energy from a turbine has the potential to generate power to car system. The wind energy is possible to integrate with other existing and renewable energy.